Information Literacy and Digital Literacy as Predictors of Students Cognitive Learning Outcomes in General Biology - Lianto Lianto; Marosa Robiatul Adawiyah; Tri Ayu Lestari (Jurnal Pijar MIPA, 2026)
The rapid digital transformation in higher education highlights the importance of literacy competencies that enable students to effectively access, evaluate, and utilize information. This study aimed to examine the relationship between information literacy (IL), digital literacy (DL), and students’ cognitive learning outcomes (CLO). A quantitative correlational design was employed involving 78 undergraduate students enrolled in a General Biology course. Data were collected using a literacy questionnaire and a cognitive test. Assumptions of normality, linearity, and multicollinearity were met prior to analysis. Multiple regression analysis revealed that IL and DL simultaneously had a significant relationship with CLO (p < 0.05; R = 0.417; R² = 0.174), while partial effects were not significant. This study demonstrates that IL and DL act as complementary rather than independent predictors of cognitive outcomes. The findings imply that integrating both literacies into instructional design is essential to enhance students’ academic performance in digital learning environments.  The study contributes to the growing literature on literacy integration in higher education and implies that instructional design should integrate information and digital literacy simultaneously to support meaningful learning and improve students’ academic performance in digital learning environments